A New Species of Cloacitrema (Digenea, Philophthalmidae) from Greater Flamingo (Phoenicopterus roseus) with Remarks on the Genera Cloacitrema and Pygorchis - Schuster, R.K. (Вестник зоологии, 2013)
Cloacitrema dubaiensis Schuster, sp. n. is described from four adult specimens found in the cloaca of greater flamingos in Dubai, UAE. It is the first Cloacitrema species found in the Afrotropic ecozone. The new species is medium-sized and slim, with the ventral sucker in equatorial position and the uterus that extends laterally to intestinal caeca. It has oval, unlobed, touching each other testes in parallel to slightly oblique position. C. dubaiensis resembles C. narrabeenensis but differs in body shape, position of acetabulum, size of the seminal vesicle and number of vitelline follicles and their extension lateral to caeca.